Development of a computational fluid dynamic model to investigate the hemodynamic impact of REBOA - Renaldo, Antonio C.; Lane, Magan R.; Shapiro, Sophie R.; Mobin, Fahim; Jordan, James E.; Williams, Timothy K.; Neff, Lucas P.; Gayzik, F. Scott; Rahbar, Elaheh (Frontiers in Physiology, 2022)
Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a lifesaving intervention for major truncal hemorrhage. Balloon-tipped arterial catheters are inserted via the femoral artery to create a temporary occlusion of the aorta, which minimizes the rate of internal bleeding until definitive surgery can be conducted. While REBOA has been successfully implemented clinically, there is growing concern over the resultant ischemia-reperfusion injury to tissues and organs downstream of the aortic occlusion. Methods: To better understand the acute hemodynamic changes imposed by full aortic occlusion with REBOA, we developed a three-dimensional (3D) computational fluid dynamic (CFD) model of a porcine aorta under normal, hemorrhage, and aortic occlusion (i.e., REBOA) conditions. The goal was to characterize the acute hemodynamic changes and identify regions within the aortic vascular tree vulnerable to abnormal flow and shear stress. Leveraging on established porcine experiments, we generated a pig-specific aortic geometry and imposed physiologically relevant inlet flow and outlet pressure boundary conditions. By assuming non-Newtonian fluid properties, pressure, velocity, shear rate, and wall shear stress were quantified. Results: We observed a significant rise in blood pressure (up to 147 mmHg) proximal to REBOA, which resulted in increased flow and shear stress within the ascending aorta. Specifically, we observed high levels of shear stress within the subclavian arteries (22.75 Pa). Alternatively, at the site of full aortic occlusion, wall shear stress was low (0.04 ± 9.07E-4 Pa), but flow oscillations were high (oscillatory shear index of 0.31). Comparatively, partial occlusion elevated shear levels to 84.14 ±19.50 Pa and reduced flow oscillations (0.05). Our numerical simulations of pressure and flow were congruent within 5% of averaged porcine experimental data over a cardiac cycle. Conclusion: This CFD model is the first to our knowledge to quantify the acute hemodynamic changes imposed by REBOA. We identified areas of low shear stress near the site of occlusion and high shear stress in the subclavian arteries. Future studies are needed to determine the optimal design parameters of endovascular hemorrhage control devices that can minimize flow perturbations and areas of high shear.